EVALUASI KEBIJAKAN PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR TAHUN 2011 DI PROVINSI SULAWESI TENGAH (STUDI PADA KOMISI PEMILIHAN UMUM PROVINSI SULAWESI TENGAH) - Mufidah, Mufidah (Katalogis, 2013)
The objective of this research is to evaluate policy in conducting Governor and Vice Governor election in Central Sulawesi held by Regional General Election Commission of Central Sulawesi Province Year 2011.This research is descriptive evaluative and based on a case study. This study described a certain phenomena from governor and vice governor election policy conducted by General Election Commission Central Sulawesi Province, while this researchÂ applied qualitative approach by collecting qualitative data obtained from interviewed. Sample of the research consisted of: (1) Pairs of Elected Governor and Vice Governor Year 2011-2016; (2) Pairs of unelected Governor and Vice Governor; (3) General Election Commission of Central Sulawesi as a caretaker of Governor and Vice Governor Election Year 2011 at Central Sulawesi Province; and (4) Regional Election Desk. This research used primary and secondary data. The data were collected through observation, interview, and questionnaire distribution. Then, the data were analyzed by using interactive analysis model. The study result showed that implementation of Governor and Vice Governor Election Central Sulawesi Province Year 2011-2016 held by General Election Commission of Central Sulawesi Province had been conducted well, correctly, safely, smoothly, and democratically. In order to support the implementation of Governor and Vice GovernorÂ electionÂ of Central Sulawesi Province period 2011-2016, General Election Commission of Central Sulawesi Province have drawn up regulation concerning the implementation of Governor and Vice Governor Election period 2011-2016 according to law constitution.